教師手勢對幼兒故事詞彙理解影響之研究 Effect of the Gestures of Teachers during Storytelling on the Vocabulary Understanding of Kindergarteners - 簡馨瑩 Hsin-Ying Chien; 連啟舜 Chi-Shun Lien (National Taiwan Normal University, 2014)
本研究分別以兩個研究解析不同年資教師於說故事時，手勢表徵的意義類別，以及手勢教學影片對幼兒在詞彙理解的影響。研究一以錄影分析的方法，探討8 位新手教師與8 位資深教師說故事時的手勢行為。結果發現，教師說故事時的手勢以描述故事內容、詞彙的語意提取性質居多；不同年資的教師於表徵故事內容的手勢次數並未有顯著差異的存在；於師生互動的手勢次數，則有顯著的差異存在。研究二分析不同年資教師的教學影片對幼兒詞彙理解的效果研究，以臺東3 所公立幼兒園大班67 位幼兒為對象進行實驗。結果顯示，資深教師的手勢教學影片對幼兒理解衍生性質的詞彙有顯著的效果。文中對未來相關研究及教師的教學手勢提出討論與建議。 This study examined the types and levels of gestures that teachers with different levels of experience used during storytelling, and investigated how these gestures affected the vocabulary understanding of children. In Study 1, the gestures of eight junior and eight senior teachers during storytelling were recorded and evaluated using the method of video analysis. The results showed that the gestures of teachers carried descriptive or semantic information related to the story. No frequency differences on gesture use were observed between junior and senior teachers to represent the story content. However, substantial differences between junior and senior teachers were observed regarding teacher-student interaction. The purpose of Study 2 was to determine whether children who watched different video clips, recorded by teachers with different levels of experience, exhibited different levels of vocabulary understanding. Sixty-seven kindergarteners in Taitung, Taiwan participated in the experiment. The results indicated that children who watched the video clip that was recorded by the senior teachers outperformed those who watched the video clip that was recorded by the junior teachers. This paper discusses implications for future research and education.